RELASI FORMULA MISTERI DALAM CERITA POPULER LIMA SEKAWAN: RAHASIA DI PULAU KIRRIN DENGAN PERKEMBANGAN KOGNITIF PADA ANAK - Ratri, Risalah Damar; Indriyani, Jiphie Gilia (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2024)
This study aims to describe the relationship between the Cawelti formula and the children's story. Lima Sekawan: Rahasia di Pulau Kirrin with cognitive development in children The research method uses a qualitative method with data obtained through a literature review. Primary data was obtained through the novel, and secondary data was obtained through related literature. Data analysis efforts were carried out in three stages, including data sorting, data grouping, and conclusion drawing. The results showed that the mystery formula in children's stories met the criteria of Cawelti's formula theory and found a mystery with a puzzle that became a conflict. The reference to the mystery formula is based on Lewis Carroll's Alice in Wonderland. The relationship between mystery formulas in children's stories and cognitive development helps cognitive development by presenting imagination in reading books that have puzzles in them. This is to train children's imagination and also spur children to hone their thinking power to participate in solving puzzles in the books they read.